Patterns of Communication in the Music Community in Relationships - Fransisca Lusianora; Made Dwi Adnjani; Dian Marhaeni Kurdaningsih; Mubarok Mubarok (Journal of Advanced Multidisciplinary Research, 2022)
This music student activity unit community of Semarang or known as ‘Kumis’, has now grown as an organization with positive goals that interest some people in joining it. This study aims to determine how communication patterns of an organization in maintaining a relationship. This study was directed to the communication patterns of the Semarang ‘Kumis’ community. This study made use of qualitative descriptive method. The technique of collecting data was conducted through participant observation supported by in-depth interviews and documentation. The subjects in this study were thirteen informants. The paradigm used in this study was the constructivist one with the sociometric theory proposed by Jacob Moreno Levy and supporting theories, such as the West Turner Groupthink theory and Group Cohesiveness as main theories. From the results of the study, it can be concluded that in maintaining relationship, the communication patterns used by the Semarang Kumis community are categorized as horizontal or literal communication patterns. The relationship maintained is akind of relationship which forms solidarity among its members through the use of information and communication technology, such as Whatsapp social media platform. Also, frequent meetings or face-to-face gatherings among members allow them to maintain open communication as to minimize communication misunderstandings and cohesiveness in the Semarang Kumis community which keep cooperation and solidarity well. The number of respondents, who was only 13 informants, is certainly not able to describe the real situation since the object of this study only focused on communication patterns. Therefore, it is expected that the results of the study can be used as an example or reference in gaining information for further studies in the same field with different research object, regarding with a community’s communication patterns in maintaining relationship.